2018
DOI: 10.1111/pops.12527
|View full text |Cite
|
Sign up to set email alerts
|

Fired Up by Morality: The Unique Physiological Response Tied to Moral Conviction in Politics

Abstract: Studies provide mounting evidence that morally convicted attitudes elicit passionate and unyielding political responses. Questions remain, however, whether these effects occur because moral conviction is another strong, versus a distinctly moral dimension of attitude strength. Building on work in moral psychology and neuroscience, I argue that moral conviction stems from a distinctive mode of mental processing that is tied to automatic affective reactions. Testing this idea using a lab experiment designed to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 110 publications
1
6
0
Order By: Relevance
“…At the same time, moral conviction has implications for political participation: It is positively associated with willingness to engage in political campaigns and activism (Ryan, 2014; Skitka et al, 2017), self-reported voter turnout, and intention to vote (Skitka & Bauman, 2008). These effects are not reducible to personality traits, political ideology, partisan identity, or attitudinal extremity (Garrett, 2019, p. 2), though moral conviction is associated with the latter.…”
Section: Moral Convictionmentioning
confidence: 99%
“…At the same time, moral conviction has implications for political participation: It is positively associated with willingness to engage in political campaigns and activism (Ryan, 2014; Skitka et al, 2017), self-reported voter turnout, and intention to vote (Skitka & Bauman, 2008). These effects are not reducible to personality traits, political ideology, partisan identity, or attitudinal extremity (Garrett, 2019, p. 2), though moral conviction is associated with the latter.…”
Section: Moral Convictionmentioning
confidence: 99%
“…Note that the negativity bias was observed not only on a psychological, but also on a physiological level. Thus, people who tend to protect the in-group against out-groups (those promoting military defense and anti-immigration policies), when being presented with threatening stimuli or images associated with out-groups, show greater attention to the threat ( Nail et al, 2009 ), as well as greater physiological arousal and sympathetic nervous system activity, measured via skin conductance ( Antony et al, 2005 ; Oxley et al, 2008 ; Dodd et al, 2012 ; Hatemi et al, 2013 ; Renshon et al, 2015 ; Garrett, 2019 ). Therefore, uncertainty and perceived threat may elevate levels of fear and anxiety in some individuals, making them less willing to embrace novel social situations or interact with new people, and be more intolerant toward members of an out-group ( Jost et al, 2003 ; Hatemi et al, 2013 ).…”
Section: In-group Vs Out-group Perceptions and Attitudesmentioning
confidence: 99%
“…She interprets this as evidence that moral language is suited for communicating extreme policy standpoints to a party's more extreme home base, but that politicians must moderate their rhetoric (i.e., deemphasize moral statements) as the audience broadens to the entire electorate and they become more concerned with appealing to the (less extreme) median voter (Lipsitz 2018). This proposition is corroborated by citizen-psychological work showing that individuals engaging in moral thinking tend to hold more extreme attitudes about the issue in question (Clifford 2019;Garrett 2019;Skitka 2010). Parties with more extreme immigration positions might therefore seek to activate moral thinking in audiences to drive the opinions of potential supporters in a more extreme direction, in greater alignment with the party stance.…”
Section: Existing Evidence On the Use Of Moral Language In Political ...mentioning
confidence: 97%